Analisis Meningkatnya Korban Kekerasan Seksual di Kabupaten Pamekasan Perspektif UU TPKS - Mahsun Ismail; Achmad Rifai; Agustri Purwandi; Salsabila Lina Rahman; Nur Rizkiyani Hafifah (Mahesa Research Center, 2026)
This paper aims to analyze the increase in victims of sexual violence in Pamekasan Regency from the perspective of the TPKS Law. This study focuses on the factors causing the increase in victims of sexual violence in Pamekasan Regency and efforts to protect and rehabilitate victims of sexual violence under Law No. 12 of 2022 concerning criminal acts of sexual violence. The research method used is a legal-normative study with a legislative approach. Legal materials were collected through literature review and analyzed using descriptive analysis. The results of the study show that, first, the factors contributing to the increase in sexual violence in Pamekasan Regency are the persistence of patriarchal attitudes, promiscuity, and the use of social media anonymity, which makes it easier for perpetrators to engage in grooming and sextortion. Infidelity occurs due to dissatisfaction in marriage, sexuality, and the need for freedom. Second, the forms of protection and recovery for victims of sexual violence regulated in the TPKS Law are stipulated in Article 66 paragraph (1), which provides legal certainty that every victim of sexual violence must receive protection from the beginning of the crime until the case is examined, tried, and decided by a panel of judges in court.